EDUCATIONAL DISCORDANCE FROM PARENTS AND LIFE SATISFACTION AMONG OLDER WHITE, BLACK, AND HISPANIC AMERICANS. (11th November 2018) - Ramirez, L; Carr, D; Taylor, M
Abstract: Previous studies have found that although economic resources increase wellbeing in the overall population, not all groups fare equally from these resources. Hispanics, in particular, are an important group to study as scholars have argued that educational gains, especially among the native born, may contrast cultural belief systems in a manner that is harmful for subjective well-being. It is not well understood how this well-being detriment is transferred, especially in the context of upward mobility across generations. This study addresses discordance in education, measured as the difference between one's own and one's parental education level, in its connection to well-being among white, black, and Hispanic older Americans. Using the Health and Retirement Study (HRS), we examine educational gains among older adults (60+) compared to their parents in connection to self-reported life satisfaction (N=8, 010). Preliminary results show older Americans report 13 years of education, on average, and gains of about 3.5 years over their parents. Hispanics reported significantly higher levels of satisfaction than any racial group. However, net of education level and other factors, education gains compared to one's parents significantly predicted decreases in life satisfaction for Hispanics, while these effects were opposite or nonsignificant in other groups. Final models will examine mechanisms of these effects by race to further explore preliminary findings. However, results indicate that upward mobility via educational gains may not confer equal benefits for well-being across racial/ethnic groups.